Gender-specific associations of anthropometric measures of adiposity with blood pressure and hypertension in young Chinese Medical College Students - Sah, Navin Kumar; Zhang, Qing-Tao; Li, Yong-Gang; Yin, Xue-Yan; Li, Li-Hua (Journal of Cardiology and Cardiovascular Medicine, 2020)
Purpose: There are uncertainties about whether general or central obesity is the more important determinant for blood pressure and hypertension in young Chinese. We aim to investigate the association between adiposity measures and blood pressure and hypertension in young medical students. Methods: A total of 380 medical students were recruited from the 2012 batch in the Clinical College of Dali University. Anthropometric measures and office blood pressure were measured. Blood pressure status was defined by Chinese hypertension guidelines and ACC/AHA 2017 hypertension guidelines, respectively. We examined the associations of adiposity measures (body weight, body mass index [BMI], waist circumference, hip circumference, waist-to-hip ratio [WHR], waist-to-height ratio [WHtR], ponderal index [PI], body adiposity index (BAI) and conicity index [CI]) with blood pressure and hypertension by sex. Results: In 380 subjects (women 66.6%, mean age 21.5 years), the prevalence of obesity (BMI ≥ 28 kg/m2) was 2.1%, and the prevalence of hypertension was 2.6% (≥ 140/90 mmHg) and 24.5% (≥ 130/80 mmHg), respectively. In correlation analyses and multivariable-adjusted linear regression analyses, most adiposity measures of central obesity were significantly associated with blood pressure in men, while in women, either adiposity measures of central or general obesity were associated with blood pressure. The predictive power of adiposity measures for hypertension was generally low in men. However, adiposity measures of either general obesity or central obesity were predictive for hypertension defined by Chinese hypertension guidelines in women. Conclusion: There are gender-specific associations of central and general obesity with blood pressure and hypertension in young Chinese medical students.